ANATOMICAL BASIS OF THE MICROSURGICAL SUTURE IN SURGICAL TREATMENT OF INGROWN NAIL - V. I. Kim; D. R. Kiriakis (Креативная хирургия и онкология, 2017)
The article describes the developed and used in clinical practice a new method of combined surgical treatment of ingrown nail, changing the anatomic form of a nail bed with microsurgical suture.